Anharmonic Effect of the Unimolecular Dissociation of HFCO and DFCO. Issue 7 (12th June 2015) - Zhong, Jingjun; Wang, Weiwen; Li, Qian; Xia, Wenwen; Shao, Ying; Yao, Li; Lin, S. H.
Abstract The unimolecular reactions of HFCO and DFCO have been studied by RRKM theory. The harmonic and anharmonic rate constants of the HFCO and DFCO decompositions have been calculated. The harmonic and anharmonic rate constants increase with the increasing temperatures and total energies both in the canonical and microcanonical systems. The comparison shows that the rate constants of DFCO decomposition are lower than that of the HFCO decomposition. The anharmonic effect and isotope effect have also been investigated. It has been found that the anharmonic effect and isotope effect are not significant either in the canonical or microcanonical system for all the reactions.